Study on the detection of active components in plasma-activated water and its storage stability - Huanlan Zhang; Momna Rubab; Moutong Chen; Jialong Gao; Qinxiu Sun; Qiuyu Xia; Zefu Wang; Zongyuan Han; Shucheng Liu; Shuai Wei (CyTA - Journal of Food)
In this study, the impact of different discharge time, discharge power, and storage time on the pH, oxidation-reduction potential (ORP), electrical conductivity (EC), H2O2, and the physicochemical properties and the stability at 4°C were evaluated. With the increase of plasma discharge time and discharge power, all the values increased except pH value. There were no significant changes in the values of pH, ORP, and EC for 30 days storage at 4°C (p > 0.05). The concentrations of NO3−, NO2−, and H2O2 exhibited significant changes (p < 0.05) after stored for 5 days. The plasma discharge time and discharge power showed significant effects on the physicochemical properties and activity of PAW. Moreover, the concentrations of NO3− and NO2− significantly affected the storage stability of PAW at 4°C.